An Analysis of the Relationship between Cognitive Flexibility and Anger in Geriatric Individuals - Pınar Harmancı; Sema İçel (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. In geriatrics, cognitive flexibility, which is known to be effective in individuals’ being patient with events, is the ability to activate one’s cognition in the face of sudden unexpected situations by processing. Being cognitively positive or negative affects geriatric individuals’ cognitive flexibility levels. It is important to examine the anger levels of geriatric individuals in the evaluation of their cognitive flexibility.